2022
DOI: 10.1111/1475-6773.14012
|View full text |Cite
|
Sign up to set email alerts
|

Best of ARM: Evaluating engagement in multisector community health networks: The case of tribal organizations

Abstract: Objective To quantify variation in public health system engagement with tribal organizations across a national sample of communities and to identify predictors of engagement. Data Sources We used 2018 National Longitudinal Survey of Public Health Systems data, a nationally representative cohort of the US public health systems. Study Design Social network analysis measures were computed to indicate the extent of tribal organization participation in public health networks and to understand the sectors and social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Multisector community partnerships are considered vital to improving health equity through social determinants of health and have been found in local public health efforts to improve population health outcomes when conditions are appropriate 5–8. However, our research group found that in regions with the presence of an AI/AN-serving health facility, just 28% of local public health jurisdictions surveyed in 2018 reported participation of tribal organizations in public health activities 9. To learn feasible ways to increase multisector community partnership with tribal organizations, the present study seeks to better understand characteristics of local public health systems with exceptional tribal organization participation.…”
mentioning
confidence: 78%
See 3 more Smart Citations
“…Multisector community partnerships are considered vital to improving health equity through social determinants of health and have been found in local public health efforts to improve population health outcomes when conditions are appropriate 5–8. However, our research group found that in regions with the presence of an AI/AN-serving health facility, just 28% of local public health jurisdictions surveyed in 2018 reported participation of tribal organizations in public health activities 9. To learn feasible ways to increase multisector community partnership with tribal organizations, the present study seeks to better understand characteristics of local public health systems with exceptional tribal organization participation.…”
mentioning
confidence: 78%
“…A retrospective, cross-sectional study was replicated to identify exceptional tribal organization participation in local public health systems in 2018 9. The original study used a logistic regression model of community characteristics to understand outcomes in tribal organization participation in public health activities 9.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Examine how multisector collaborations can improve healthcare equity for marginalized populations 68. Technology (e.g., telehealth, eHealth, mHealth, health information) is increasingly incorporated in healthcare delivery of interventions.69,70 As technology is increasingly being used in healthcare systems to improve care, it is important to ensure such technologies do not exacerbate inequities.…”
mentioning
confidence: 99%